Multiple classifier systems 10th International Workshop, MCS 2011, Naples, Italy, June 15-17, 2011. Proceedings - Sansone, Carlo 1969-; Kittler, Josef 1946-; Roli, Fabio 1962- (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 10th International Workshop on Multiple Classifier Systems, MCS 2011, held in Naples, Italy, in June 2011. The 36 revised papers presented together with two invited papers were carefully reviewed and selected from more than 50 submissions. The contributions are organized into sessions dealing with classifier ensembles; trees and forests; one-class classifiers; multiple kernels; classifier selection; sequential combination; ECOC; diversity; clustering; biometrics; and computer security.